To write the given quadratic equation to its vertex form, we first form a perfect square.
x² - 2x + 5 = 0
Transpose the constant to other side of the equation,
x² - 2x = -5
Complete the square in the left side of the equation,
x² - 2x + (-2/1(2))² = -5 + (-2/1(2))²
Performed the operation,
x² - 2x + 1 = -5 + 1
Factor the left side of the equation,
(x - 1)² = -4
Thus, the vertex form of the equation is,
<em> (x-1)² + 4 = 0</em>
Step-by-step explanation:
(1+3x-1)×{1-(3x-1)}
=3x.(1-3x+1)
=3x.3x
=9x^2.
Answer:
Step-by-step explanation:
f
(
x
)
=
−
4
(
x
−
8
)
2
+
3
Set the polynomial equal to
y
to find the properties of the parabola.
y
=
−
4
(
x
−
8
)
2
+
3
Use the vertex form,
y
=
a
(
x
−
h
)
2
+
k
, to determine the values of
a
,
h
, and
k
.
a
=
−
4
h
=
8
k
=
3
Since the value of
a
is negative, the parabola opens down.
Opens Down
Find the vertex
(
h
,
k
)
.
(
8
,
3
)
Find
p
, the distance from the vertex to the focus.
Tap for more steps...
−
1
16
Find the focus.
Tap for more steps...
(
8
,
47
16
)
Find the axis of symmetry by finding the line that passes through the vertex and the focus.
x
=
8
image of graph
I honestly don’t even know how to explain this- but ik that 3 should be alright to type in bc if you were to write it on a graph you would move 1 unit to the right and 3 units up from there based on the coordinates after the origin (0,0).